Effect of Transformational Leadership Style and Work Commitment on Employee Performance at the Regional Secretariat of Murung Raya Regency, Central Kalimantan Province - Yohana; Humaidi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
This study aims to determine the Effect of Transformational Leadership Style and Work Commitment on Employee Performance at the Regional Secretariat of Murung Raya Regency, Central Kalimantan Province. The technique used in this study is SmartPLS Analysis using the help of the SmartPLS package computer program with a significance level of 5 percent by using questionnaires as primary data. The population in this study were employees of the Regional Secretariat of Murung Raya Regency as many as 192 people with a sample of the same number as many as 192 respondents who used saturated sampling techniques, that is, the entire population was sampled. The results of this study indicate that partially transformational leadership style and work commitment have a significant effect on employee performance, this means that an increase in transformational leadership style and work commitment will improve employee performance at the Murung Raya Regency Regional Secretariat. To maintain employee performance at the Murung Raya Regency Secretariat, it can be done by using transformational leadership styles and managing work commitments. It is important to take actions that can improve work commitment and employee performance